Information theoretic approach to complexity reduction of FIR filter design - Chang, Chip Hong (2010)
This paper presents a new paradigm of design.methodology to reduce the complexity of application-specific finite-impulse response (FIR) digital filters. A new adder graph data structure called the multiroot binary partition graph (MBPG) is proposed for the formulation of the multiple onstant multiplication problem of FIR filter design. The set of coefficients in any fixed point representation is partitioned into symbols so that common subexpression identification and elimination become congruent to